A Qualitative Analysis of Parents With Children Diagnosed With Reading Disabilities: Insights for Working With Families. (January 2015) - Dipeolu, Abiola; Storlie, Cassandra; Hargrave, Stephanie J.; Cook, Robin
Semistructured interviews were conducted with nine parents with children diagnosed with reading disability (RD). A phenomenological theoretical tradition was used to explore the meaning, structure, and essence of the shared experiences of these individuals. Results generated a deeper understanding of the lived experiences and challenges of families with children diagnosed with RD. Themes produced a need for a systemic model of home, school, and community collaboration, which may improve interaction and communication among all parties. Implications for research and working with families with children diagnosed with RD are discussed.